Pengaruh Model Pembelajaran Read, Answer, Discuss, Explain, and Creat (RADEC) terhadap Kemampuan Menulis Teks Eksposisi Siswa Kelas X SMA Negeri 11 Medan Tahun Pembelajaran 2023/2024 - Sirait, Lilis Suryanti; Wasilah, Atika (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This study aims to determine the effect of RADEC learning model on the ability to write exposition text of X-grade students of SMA Negeri 11 Medan. The subjects in the study were students of class X SMA Negeri 11 Medan with a sample of 36 students. The sampling technique was cluster random sampling. The method used was experimental with one group pre-test and post-test design. The results of the study before using the RADEC learning model obtained an average of 64,58. The results after using the RADEC learning model obtained an average of 80,89. The pretest-posttest normality test results prove normal distribution, as well as the homogeneity test which proves that the sample is from a homogeneous population. After that, it is known that the tcount is 9,11. Furthermore, the value was consulted at a significant level ? = 0,05 with dk n-1 (36-1) = 35, obtained t table = 1,68. Thus it can be concluded that tcount> ttable is 9,11> 1,68, so that the null hypothesis (HO) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a significant effect of using the RADEC learning model on the ability to write expository texts of class X SMA Negeri 11 Medan students in the 2023/2024 learning year.